Importance of Marketing in Tourism and Hotel Industry - Ruziev Sobirjon Samatovich (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The article focuses on the marketing objectives in tourism and the hotel industry, i.e. how to create the conditions for tourism enterprises to achieve their goals and how to sell them to the market. In addition, the marketing functions in tourism and the hotel industry are usually clarified based on the marketing functions of tourism enterprises. The important task of marketing in the article will be to ensure as much stability as possible in the activities of tourism enterprises, to submit to planning in the development and achievement of strategic goals. If you do not pay attention to the specific problems that arise in the field of services, tourism marketing can be divided into several groups of tasks. Furthermore, in this article, we will look at several stages of marketing tasks.